Implementation of The Learning Value of Pancasila and Citizenship Education in Religious Moderation Activities - Siti Fatikhatus Syaadah; Zaenul Slam (Jurnal Civicus, 2023)
The implementation of religious moderation through Pancasila and citizenship education is the subject of discussion in this research. Indonesia is known as a multicultural country, and to create peace, of course, requires the role of religious moderation to avoid problems that occur in society. In this research, religious moderation is discussed in terms of its comprehension, how it is taught in Pancasila and citizenship education, and how it is put into practice. A review of literature is used in this research, methodology through analysis of literature from various existing sources. Through this research, it was found that religious moderation is a fair and balanced behavior in practicing a concept by applying a moderate attitude in life to create a harmonious and peaceful life.